Aplikasi Sistem Informasi Geografis untuk Pemetaan Potensi Banjir di Kawasan Pariwisata Ubud Provinsi Bali - Arsyila Nafisa Muftiara; I Wayan Diara; R. Suyarto (Fakultas Pertanian, Universitas Udayana, 2023)
The Ubud Tourism Area is a tourism area which is located on a fairly high plateau but floods often occur, especially when rainfall is high. The parameters causing potential flooding in the Ubud Tourism Area are river distance, altitude, slope, rainfall, land use and soil type. The purpose of this study is to provide information on the distribution of potential flooding in the Ubud Tourism Area in the form of mapping related to the awareness of the public and tourists against flood disasters. This research was conducted in Ubud District from October 2022 to January 2023. The research method used is the scoring and weighting method as well as the overlay of the parameters that cause potential flooding. The OSM Tracker application is used for field checking by checking potential flood points spread out in the study area. The results of the study show that there are five classes of potential flooding, namely very low, low, medium, high and very high. The potential for flooding in the Ubud Tourism Area is dominated by the high class area of 1,844.21 ha (43.02%) of the total area of Ubud District. Then very low class area of 15.91 ha (0.37%), low area of 408.16 ha (9.52%), medium area of 1587.25 ha (37.02%) and very high 432.4 ha (10 .08%) of the area of the Ubud Tourism Area.